Numerical simulations of regolith sampling processes. (July 2017) - Schäfer, Christoph M.; Scherrer, Samuel; Buchwald, Robert; Maindl, Thomas I.; Speith, Roland; Kley, Wilhelm
Abstract: We present recent improvements in the simulation of regolith sampling processes in microgravity using the numerical particle method smooth particle hydrodynamics (SPH). We use an elastic-plastic soil constitutive model for large deformation and failure flows for dynamical behaviour of regolith. In the context of projected small body (asteroid or small moons) sample return missions, we investigate the efficiency and feasibility of a particular material sampling method: Brushes sweep material from the asteroid's surface into a collecting tray. We analyze the influence of different material parameters of regolith such as cohesion and angle of internal friction on the sampling rate. Furthermore, we study the sampling process in two environments by varying the surface gravity (Earth's and Phobos') and we apply different rotation rates for the brushes. We find good agreement of our sampling simulations on Earth with experiments and provide estimations for the influence of the material properties on the collecting rate. Abstract : Highlights: The sampling of material on Phobos' surface is investigated with numerical modelling. Smooth Particle Hydrodynamics can be successfully applied to model Regolith. The sampling rate depends on the cohesion and angle of internal friction of Regolith.